2020
DOI: 10.1007/s43465-020-00226-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Orthopaedic Trauma Volumes: a Multi-Centre Perspective From the State of Telangana

Abstract: Background The COVID-19 outbreak reached pandemic proportions in March 2020, and the government of India declared a nationwide lockdown on 24th March, 2020. All vehicular movement, construction work, industries, national highways, etc. remained closed during lockdown. The aim of this study was to assess the impact of lockdown on the case load and epidemiology of orthopaedic trauma cases in the state of Telangana. Methods This study was a multi-centre, retrospective obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 3 publications
1
63
0
1
Order By: Relevance
“…A tertiary centre in London that did not alter its threshold for surgery based on this recommendation noted a decrease in surgical cases of one‐third compared to pre‐pandemic, suggesting that the primary driver of decreased procedures was decreased referral volume, rather than local protocol 13 . Similar decreases in trauma referrals have been recognized in centres in the USA, 14 Spain 15 and India 16 …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A tertiary centre in London that did not alter its threshold for surgery based on this recommendation noted a decrease in surgical cases of one‐third compared to pre‐pandemic, suggesting that the primary driver of decreased procedures was decreased referral volume, rather than local protocol 13 . Similar decreases in trauma referrals have been recognized in centres in the USA, 14 Spain 15 and India 16 …”
Section: Discussionmentioning
confidence: 70%
“…13 Similar decreases in trauma referrals have been recognized in centres in the USA, 14 Spain 15 and India. 16 Physical distancing requirements and mandatory shutdown of businesses, workplaces and gatherings have transformed daily activities. The Citimapper Mobility Index estimates the movement of people within Sydney decreased by up to 84% in March, as fewer people utilized public transport or drove to their places of work.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the number of fractures decreased sharply in all 13 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 but one 32 of the included studies. Although the total number of fractures was reduced by 43% (35–50%) during the pandemic, we found that the proportion hand fractures was lower (significant), the proportion of femur fractures was higher (borderline significance), whereas the proportion of fractures at other locations was relatively constant.…”
Section: Discussionmentioning
confidence: 92%
“…Since the beginning of COVID-19 epidemic, the incidence of orthopaedic trauma admission has declined substantially given the widespread implementation of self-isolation, quarantine, lockdown, and travel restrictions. 13 , 14 , 15 , 16 People are urged to stay at home and only seek medical services if they experience a medical emergency. Reduction on public mobility and outdoor activities contributed to the decrease in motor vehicle accidents, sport-related traumas, and work-related traumas.…”
Section: Introductionmentioning
confidence: 99%
“…Hip fracture is a surgical emergency. Despite mandatory lockdown during COVID-19 pandemic, hip fracture incidence has remained unaltered[ 2 - 5 ].…”
Section: Introductionmentioning
confidence: 99%